In Vitro Inhibition of Growth and Induction of Apoptosis by Mosinone-A in HEp-2 Oral Cancer Cells: Life Sciences-Biochemistry - Govindasamy, Sugunadevi; Kathiresan, Suresh; Rengaraj, Gomathi (International Journal of Life Science and Pharma Research, 2023)
The present study evaluated the influence of a Mosinone-A on the induction of apoptosis in HEp-2 human pharyngeal carcinoma cell lines as evidenced by cytotoxicity morphological changes, inhibition of cell proliferation in a time and dose dependent manner. Oral cancer is one of the leading causes of cancer worldwide. Many chemotherapeutics from plants have been tested in cancer, such as Mosinone-A, isolated from the bark of Annona squamous, acetogenin. further we analyzed anticancer activity by MTT assay, the generation of reactive oxygen species (ROS), the level of mitochondrial membrane potential and apoptotic morphological changes were analyzed by AO/EtBr. The results of an MTT assay demonstrated that Mosinone-A inhibited the growth of HEp2 cells in a dose-dependent manner. In addition, the induction of apoptosis was detected, as determined by morphological observation. These results indicated that Mosinone-A may induce apoptosis of HEp2 cells through the mitochondrial pathway.